PIC16F1847 MICROCONTROLLER-BASED PROGRAMMABLE LOGIC CONTROLLER, THREE VOLUME SET - Uzam, Murat, 1968- ([S.l.] : CRC PRESS, 2020)
Programmable logic controllers (PLCs) have been used extensively and are offered in terms of functions, program memories, and the number of inputs/outputs (I/Os), ranging from a few to thousands. With a focus on how to design and implement a PLC, this set explains hardware and associated basic concepts, intermediary and advanced concepts of PLC (using PIC16F1847 microcontroller). Flowcharts are provided to help the understanding of macros (instructions). Twenty application examples to show how to use the PIC16F1847-Based PLC in different control applications, related files for hardware and software components, and appendices are also provided. Aimed at researchers and graduate students in electrical engineering, power electronics, robotics and automation, sensors, this book: Explains how to design and use a PIC16F1847 microcontroller-based PLC including easy to use software structures. Covers concepts like Contact and Relay Based Macros, Flip-Flop Macros, Timer Macros, Counter Macros and Comparison Macros. Presents arithmetical and logical macros to carry out arithmetical and logical operations to be used for 8-bit or 16-bit variables and/or constant values. Illustrates program control macros to enable or disable a block of PLC program or to move execution of a program from one place to another. Discusses the implementation of Sequential Function Chart (SFC) elements with up to 24 steps.
OCLC-licensed vendor bibliographic record.
Keywords: PIC microcontrollers; Logic circuits; Programmable logic devices; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / General; TECHNOLOGY / Electronics / Circuits / General